Assessment of Biological Carbonation Strategies in the Marine Ecosystem and Potential Applications in Cementitious-Based Products via a Biomimetic Model - Letícia Bonassa Severino; Gustavo Muniz Dias; Silvia Titotto (Proceedings)
The increase in the concentration of greenhouse gases of anthropogenic origin, especially carbon dioxide, concerns different spheres of society. In light of this, efforts, such as carbon capture and utilization, are being made to ensure the temperature addition limit of 1.5 °C is not exceeded by 2100. Within this scenario, the construction sector presents itself critically, especially due to cement, which accounts for between 7% and 8% of global carbon dioxide emissions. It is known that during the life cycle of cementitious materials, a natural carbonation process occurs, where CO2 is reincorporated into the cementitious matrix. Thus, this study sought to investigate the biological processes related to carbon capture and utilization for structural consolidation in order to assimilate the strategies applied in nature. It also sought to assess the viability of replication in artificial processes as a mechanism for enhancing the carbonation that occurs in the life cycle of cementitious materials, incorporating environmental intelligence to address environmental and urban challenges. A literature review confirmed the potential benefit of carbon capture, utilization, and storage inspired by the biomineralization process, and this can be observed in the marine ecosystem. Additionally, the relevance of oceans as a source of knowledge for the development of new solutions is highlighted. As an additional contribution of the study, the detailed process of biomimetic thinking presented throughout the discussion is highlighted, emphasizing the multidisciplinary scope necessary to ensure the understanding of design strategies.